Usage of Mobile Payment System-Integrating Social Influence as A Factor to Apprehend Intention to Use (International Journal of Environmental Sciences, 2025)
To examine the important factors determining the intent to use mobile payment, relationships among constructs, and propose a model to integrate social influence and mindfulness as a factor to understand intention to use in the context of a mobile payment system. The data were collected among students and faculty using an online survey method. The SEM method was employed to examine the relationship among constructs. The findings revealed that Social influence as a construct is positively influencing Intention to use the mobile payment system. The results further reveal that mindfulness, perceived ease of use, and perceived usefulness influence attitude, which in turn leads to Intention to use. The mobile payment app developers would incorporate the social influence as a construct that considers how an individual is greatly influenced by social circles, like friends, in getting motivation to adopt the mobile payment system.